2017
DOI: 10.1007/s10637-017-0525-1
|View full text |Cite|
|
Sign up to set email alerts
|

Phase Ib/II study of gemcitabine, nab-paclitaxel, and pembrolizumab in metastatic pancreatic adenocarcinoma

Abstract: Background A single center phase Ib/II study of gemcitabine, nab-paclitaxel, and pembrolizumab (GNP) to evaluate the safety and efficacy in metastatic pancreatic adenocarcinoma (PDAC) was conducted (NCT02331251). Methods PDAC patients (pts) with measurable disease, biopsy proven metastasis, adequate laboratory tests, and KPS ≥ 70% received GNP until progression or toxicity. Safety monitoring, RECIST 1.1, and irRECIST assessments were conducted. Response imaging was performed prior to cycle 4, then every 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 23 publications
2
111
1
Order By: Relevance
“…Recently, plasma CNI has been increasingly used as a prognostic marker for pancreatic cancer [9] and head and neck squamous cell carcinoma [10]. In accordance with these results, we found that a high CNI could be an independent marker for unfavorable prognosis in patients with resectable GC.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Recently, plasma CNI has been increasingly used as a prognostic marker for pancreatic cancer [9] and head and neck squamous cell carcinoma [10]. In accordance with these results, we found that a high CNI could be an independent marker for unfavorable prognosis in patients with resectable GC.…”
supporting
confidence: 88%
“…All patients had undergone adjuvant chemotherapy with capecitabine plus oxaliplatin (XELOX). The median number of chemotherapy cycles was 6 (range, [3][4][5][6][7][8][9][10][11][12]. Overall survival (OS) was defined as the time from surgery to death or the last follow-up.…”
Section: Dear Editormentioning
confidence: 99%
“…The CTLA-4 inhibitor tremelimumab in combination with weekly gemcitabine demonstrated preliminary efficacy and tolerability with the most common grade 3-4 toxicities being asthenia (11.8%) and nausea (8.8%) in a phase Ib trial enrolling treatment-naïve metastatic pancreatic cancer patients [48]. A dose-finding, multi-arm phase Ib trial enrolled patients with advanced solid tumors to 6 different treatment arms; in the metastatic PDAC cohort, a final 17 patients with treatment-naïve or previously-treated disease received combination pembrolizumab, gemcitabine, and nab-paclitaxel with responses observed only in those who were previously untreated (Table 2) [49,50]. Notably, gemcitabine and nab-paclitaxel were reduced to 800 mg/m 2 and 100 mg/ m 2 in the pretreated cohort, which was ultimately closed 2 PRs with OS after onset of therapy of 13 and 5 mos due to futility [50].…”
Section: Chemotherapymentioning
confidence: 99%
“…A dose-finding, multi-arm phase Ib trial enrolled patients with advanced solid tumors to 6 different treatment arms; in the metastatic PDAC cohort, a final 17 patients with treatment-naïve or previously-treated disease received combination pembrolizumab, gemcitabine, and nab-paclitaxel with responses observed only in those who were previously untreated (Table 2) [49,50]. Notably, gemcitabine and nab-paclitaxel were reduced to 800 mg/m 2 and 100 mg/ m 2 in the pretreated cohort, which was ultimately closed 2 PRs with OS after onset of therapy of 13 and 5 mos due to futility [50]. Immune-related AEs (all grades) were seen in 47.1%.…”
Section: Chemotherapymentioning
confidence: 99%
“…• Weiss et al reported findings from the metastatic PDA patient arm of the NCT02331251 trial [11]. In this phase I/II study, 17 patients were treated with the combination of gem, nab, and pembrolizumab.…”
Section: Introductionmentioning
confidence: 99%